Ethical aspects of professional dilemmas in the first year of teaching. Issue 2 (15th March 2017) - Ulvik, Marit; Smith, Kari; Helleve, Ingrid
Abstract : Education is described as a moral enterprise and many of the professional dilemmas teachers encounter have an ethical aspect. Research on ethical situations that novice teachers experience, however, seems to be limited, and we know little about how teacher education can prepare student-teachers for dealing with ethical issues. In this article a narrative approach is used to examine what kind of dilemmas with ethical aspects new teachers in upper secondary school in Norway may experience. The findings suggest that their dilemmas are related to the induction phase in teaching, and that the students are unprepared for dealing with these dilemmas. Based on what we learned from the new teachers, we suggest various implications for teacher education about how to prepare future teachers for handling the variety of professional dilemmas including ethical aspects they are likely to meet.